A articulação da instrumentalidade no exercício profissional do assistente social em Natal/RN - Cortes, Sarah Tavares (2013)
Presents the discussion of practical and social dimensions that comprise the instrumentality (formative; theoretical and intellectual; investigative; technical-instrumental; and ethical-political) Social Work from research in social and occupational areas in which they operate social workers in Natal in Rio Grande do Norte. Chapters expose positions, experiences and reality of the respondents and the theoretical constructs and analytical, to understand: the evaluation of the training process, relating the teaching practice, the role of knowledge and the importance of research in professional practice of social workers, the seizure of technical-instrumental dimension, articulating demands, duties, powers and instruments, as elements that comprise it, and finally the ethical-political dimension, discussing the challenges of ethics and materialization of the ethical-political in daily work. In this sense, the dissertation sought add to production and academic debate about the work of the social worker, as well as contribute to their own professional practice, revealing how professionals articulate the practical and social dimensions that comprise the instrumentality in their daily work